2020
DOI: 10.33508/bw.v8i1.2126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Story Reading on Incidental Lexical and Grammatical Collocation Learning by Iranian EFL Learners

Abstract: The purpose of the present study was to investigate the effect of story reading on incidental lexical and grammatical collocation learning. Moreover, it was an attempt to scrutinize whether there was any significant difference between incidental lexical and grammatical collocation learning. To this end, 36 Iranian EFL learners attending Sadra English Institute in Yasuj participated in the study. They were selected based on the result of quick placement test (QPT) as 28 out of 36 elementary EFL learners. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Under the condition of incidental vocabulary learning, besides mastering meaning and form of words, the usage of words is more likely to be gained. Mina and Fatemeh (2020) revealed that it is significant to gain grammatical collocation knowledge from story reading.…”
Section: Different Modes Of Input Versus Incidental Vocabulary Learningmentioning
confidence: 99%
“…Under the condition of incidental vocabulary learning, besides mastering meaning and form of words, the usage of words is more likely to be gained. Mina and Fatemeh (2020) revealed that it is significant to gain grammatical collocation knowledge from story reading.…”
Section: Different Modes Of Input Versus Incidental Vocabulary Learningmentioning
confidence: 99%